A mixed-valent CuI/CuII metal–organic framework with selective chemical sensing properties. Issue 44 (28th October 2016) - Jiao, Chengli; Jiang, Xia; Chu, Hailiang; Jiang, Heqing; Sun, Lixian
Abstract : A 3D mixed-valent Cu I /Cu II metal–organic framework with high sensitivity to water over organic solvents has been synthesized and characterized. Abstract : A novel 3D mixed-valent Cu I /Cu II metal–organic framework has been solvothermally synthesized and characterized by single-crystal X-ray diffraction, photoluminescence spectroscopy, thermal gravimetric analysis, and powder X-ray diffraction. The structure possesses a 3D open framework constructed from the linkages of 1D [Cu I (4, 4′-bipy)] n chains with [Cu II (oda)2 ] 2− cationic subunits. The chemical sensing properties of this MOF have been studied by the quartz crystal microbalance technique. The framework exhibits good selectivity and sensitivity to water with respect to other organic solvents in view of chemical sensing applications.